2018
DOI: 10.1111/soru.12209
|View full text |Cite
|
Sign up to set email alerts
|

Retired Farmers and New Land Users: How Relations to Land and People Influence Farmers' Land Transfer Decisions

Abstract: Access to land is a key challenge for prospective farmers in Europe. Retiring family farmers who lack a successor resort to leasing or selling their land, but the decision has implications for the community and the rural landscape for generations to come. It is thus crucial to know more about values and decisions linked to keeping, leasing or selling land, and the opportunities these provide for young farmers seeking to establish a business. It is also important to consider the choice of lessee/buyer and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 36 publications
1
23
0
1
Order By: Relevance
“…Although the current research on "global land grabbing" [9,[35][36][37][38] has enriched the understanding of the roles of various actors and factors involved in land deals, no study has identified, so far, the factors that can influence the landowners' decision to refuse to sell the land even when a good price is offered. Thus, while other studies investigated the people's reasons for persistent landownership in the rural-urban fringe [39] or land attachment in general [40][41][42], this is the first attempt to reveal factors contributing to Romanian landowners' resistance to sell within the foreign land grabbing context.…”
Section: Introductionmentioning
confidence: 99%
“…Although the current research on "global land grabbing" [9,[35][36][37][38] has enriched the understanding of the roles of various actors and factors involved in land deals, no study has identified, so far, the factors that can influence the landowners' decision to refuse to sell the land even when a good price is offered. Thus, while other studies investigated the people's reasons for persistent landownership in the rural-urban fringe [39] or land attachment in general [40][41][42], this is the first attempt to reveal factors contributing to Romanian landowners' resistance to sell within the foreign land grabbing context.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that where no successor can be designated, or the successor is not ready to take over the farm, farmers tend to continue to gradually wind down their business rather than selling up or leasing the land out to younger farmers outside the family a phenomenon termed the 'retirement effect' [22]. Long-term land leasing offers landowners, who may want to retire from farming, the opportunity to earn stable and long-term income from their land while ensuring the maintenance of the land, machinery and associated farm buildings without any fear of disruption in their income stream [22,72]. Long-term land leasing also ensures ownership of the land is retained should a successor require it in the future.…”
Section: Easy Retirement Decisionmentioning
confidence: 99%
“…Generally, farmers identify themselves strongly with their farmland and its sense of place, across both space and time, which can make it difficult for them to consider disengaging from active farming and engaging in longer-term land leasing [46]. There is always the desire to continue the family tradition in farming, with a sense of duty to be custodians of the land and a desire to keep the farm operational for future generations [46,72]. Farming on owned land rather than leasing the land has been described as providing the farmer with identity, occupation, control, and status in the community as well as social and cultural capital.…”
Section: The Desire To Keep Land In the Family Namementioning
confidence: 99%
“…In the case of information service related to cultivated items for returnees, when users select cultivated items and comparative items, comparative information on the number of farm households, area, facility area, road area, self-cultivation area, and lease area is provided for the item. However, there is a problem in which it is difficult to find the meaning of providing the information [7].…”
Section: Existing Research Analysismentioning
confidence: 99%